ChemInform Abstract: Rechargeable Magnesium Battery: Current Status and Key Challenges for the Future. Issue 28 (July 2015) - Saha, Partha; Datta, Moni Kanchan; Velikokhatnyi, Oleg I.; Manivannan, Ayyakkannu; Alman, David; Kumta, Prashant N.
Abstract Review: 239 refs.